Provision of deworming intervention to pregnant women by antenatal services in countries endemic for soil-transmitted helminthiasis. - Mathieu Bangert; Pilar Bancalari; Denise Mupfasoni; Alexei Mikhailov; Albis F Gabrielli; Antonio Montresor (Public Library of Science (PLoS), 2019)
Background The World Health Organization has recently reemphasized the importance of providing preventive chemotherapy to women of reproductive age in countries endemic for soil-transmitted helminthiasis as they are at heightened risk of associated morbidity. The Demographic and Health Surveys (DHS) Program is responsible for collecting and disseminating accurate, nationally representative data on health and population in developing countries. Our study aims to estimate the number of pregnant women at risk of soil-transmitted helminthiasis that self-reported deworming by antenatal services in endemic countries that conducted Demographic and Health Surveys. Methodology/principal findings The number of pregnant women living in endemic countries was extrapolated from the United Nations World Population Prospects 2015. National deworming coverage among pregnant women were extracted from Demographic and Health Surveys and applied to total numbers of pregnant women in the country. Sub-national DHS with data on self-reported deworming were available from 49 of the 102 endemic countries. In some regions more than 73% of STH endemic countries had a DHS. The DHS report an average deworming coverage of 23% (CI 19-28), ranging from 2% (CI 1-3) to 35% (CI 29-40) in the different regions, meaning more than 16 million pregnant women were dewormed in countries surveyed by DHS. The deworming rates amongst the 43 million pregnant women in STH endemic countries not surveyed by DHS remains unknown. Conclusions/significance These estimates will serve to establish baseline numbers of deworming coverage among pregnant women, monitor progress, and urge endemic countries to continue working toward reducing the burden of soil-transmitted helminthiasis. The DHS program should be extended to STH-endemic countries currently not covering the topic of deworming during pregnancy.